Of troubled times a comparative analysis between biblical prophecies in the book of revelation and the interpretative illustrations in the chick publication's crusades - Hisuan, Jan Kristan (2016.)
Adapting other media materials to comic books is not common, especially if it is from one print medium to another. One of the hardest printed material to be put into comic books is the Bible because it deals with the abstract concept of faith and the interpretation varies from one person to another. Biblical interpretation can yield one-sided information about the Bible and will stir issues and controversy among people of variant religions. This research analyzes the content of the comic book and how it interpreted the Bible. The research focuses on the comparison and alignment between the Bible verses in the Book of Revelation that talks about prophecies and the comic books? pictorial and textual interpretation of these prophecies of the last days. Several instances of manipulation from the Comic books have been found. Manipulative occurrences were evident through the use of footnotes and referencing and with the probable effect of taking a verse out of context when being quoted. Illustrations can also be manipulative with the author?s own concept of beings and places that are non-existent on earth. It was further deemed that the religious leaders may have reservations in recommending the reading of the comic books by their congregation
Thesis -- Bachelor of Arts in Communication and Media Studies. University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Comic books; Bible; Interpretation -- Bible; Book of revelation; Hermeneutics; Semantics